The culture of sectarianism : community, history, and violence in nineteenth-century Ottoman Lebanon - Makdisi, Ussama Samir, 1968- (University of California Press, 2000)
Focusing on Ottoman Lebanon, this book shows how sectarianism was a manifestation of modernity that transcended the physical boundaries of a particular country. It challenges those who have viewed sectarian violence as an Islamic response to Westernization or simply as a product of social and economic inequities among religious groups.